The Influence of Family and School in Shaping the Values of Children and Young People in the Theory of Free Time and Pedagogy - Kralik, Roman (Journal of Education Culture and Society, 2023)
Aim. The aim of the paper was to point out that the hierarchy of values is considered the most reliable prognostic sign that expresses whether a person can behave in accordance with his environment. The author identifies the causes of the current crisis of value orientations, discusses the influence of family and school on the creation and transformation of values in the lives of young people.Methods. Through analytical-synthetic and inductive methods, the author identifies the influence of consumer society and family on the creation of value systems of children and youth. It points to the pedagogy of free time and its connection to the theories and functions of free time.Results. The author provides a summary of theoretical meanings, summaries and theories in the field of value orientation of children and youth, discovered factors that influence the development and formation of value orientation, discovered the share of family, peers and free time in the creation of a value ranking.Conclusions. Any changes in society brought a wider spectrum of information, freedom of speech, opportunities for social mobility and education, but also deepening of social inequality, deterioration of interpersonal relations, moral relativism and value chaos. Current problems of society's development and their solution also affect the way of life of young people, the process of its quantitative changes, including attitudes to life and value orientation.